Peran Kepala Sekolah Dalam Memotivasi Kinerja Guru dI MTs Darun Najah Karangploso Malang - Annafisatul Qonitah (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2020)
The efforts of the principal in motivating teacher performance are very important to be investigated, especially at MTs Darun Najah because there is high enthusiasm from the teachers in carrying out their duties, as well as the principal who is pro-active in carrying out his role to always motivate all teachers. Therefore, this study aims to explore the role of the principal and the efforts made by the principal in motivating teacher performance at MTs Darun Najah.Based on the research context above, the researcher has the aim of (1) To describe the role of the principal in motivating teacher performance. (2) To find out the efforts made by the Principal to motivate the performance of Teachers at MTs Darun Najah. The type of research used by the writer is descriptive qualitative, while the method for collecting data is the method of interview, observation, and documentation taken from the principal, teachers and employees. Then performed data analysis by means of data reduction, presenting data and drawing conclusions. And finally checking the validity of the data by correcting the research method used, double-checking the results of the report in the form of descriptive data and triangulation is carried out to ensure the objectivity of the research.From the research conducted, it can be seen that the principal of MTs Darun Najah school has played a good role in motivating the performance of teachers at MTs Darun Najah starting from their role as educator, manager, administrator, supervisor, leader, innovator, and motivator. Some of the efforts made by the principal in motivating teacher performance by creating a safe and comfortable work atmosphere, as well as providing rewards and punishments to teachers who excel and violate rules, and always provide messages that can foster teacher motivation at work.